Ramat Raḥel IV: the renewed excavations by the Tel Aviv-Heidelberg expedition (2005-2010) : stratigraphy and architecture - Lipshits, ʿOded; Oeming, Manfred; Gadot, Yuval (Monograph series of the Institute of Archaeology, Tel Aviv University, 2020)
Intro -- COVER Front -- Copyright Page -- Table of CONTENTS -- Chapter 1: STRATEGIC LOCATION AND NATURAL SURROUNDINGS -- Chapter 2: THE ANCIENT NAME OF THE SITE -- Chapter 3: HISTORY OF RESEARCH -- Chaptr 4: THE RENEWED EXCAVATIONS BY THE TEL AVIV-HEIDELBERG EXPEDITION -- Chapter 5: AREAS A1, B1 AND B3,WITH AN EMPHASIS ON THE CEMETERY -- Chapter 6: AREA B2 -- Chapter 7: AREA C1 -- Chapter 8: AREA C2 -- Chapter 9: AREA D1 -- Chapter 10: AREA D2 -- Chapter 11: COURTYARD 380, THE INNER GATE AND BUILDING 468 -- Chapter 12: AREA D4 -- Chapter 13: AREA D6.